A study on the rights of children born out of wedlock to inherit property from their 'parents'/ Aaina Liyana Abd Manaf…[et al.] - Abd Manaf, Aaina Liyana; Razali, Nurulyazmine; Mohd. Ridzuan, Nur Nadeera; Benedick, Amanda Leonie (2009)
This thesis deals with the law of inheritance in Malaysia. It concerns the rights of illegitimate children to inherit property from their 'parents'. The main objective of this research is to make a fair comparison between the two different laws, i.e. Islamic law and also civil law and to lay down the rights of inheritance of the illegitimate children. Basically, the general rule in both laws is that only legitimate persons are entitled to inherit. Our first impression regarding the title of our research was that illegitimate children are generally prohibited to get inheritance. However, after studying the laws critically and carefully, we found out that illegitimate children do indeed have rights to inheritance. Legitimacy is the key to inheritance. Therefore, we believe that we ought to discuss into detail of the law of legitimacy and how one's status can be illegitimate. For Muslims, the law that governs them is the divine words of Allah in the Holy Quran. Islam has set out strict rules regarding the rules of inheritance. With such rigidity, it is impossible to alter the position of illegitimate children under inheritance. However, an illegitimate child is considered as the child of his mother and thus, his rights to inheritance lie with the mother. For non-Muslims, the laws available are the Distribution Act 1958, Inheritance Act 1971 and Wills Act 1959. There is no provision under the civil law specifically stating that an illegitimate child cannot inherit from his or her 'parents' but the law provides an alternative for these illegitimate children to inherit and that is, by way of legitimization. The process of legitimization makes the illegitimate child to be legitimate and therefore, makes the child as the lawful child of his 'parents' or adopted parents.